Fused Thiophene‐Pyrrole‐Containing Ring Systems up to a Heterodecacene1. Issue 42 (1st July 2015) - Wetzel, Christoph; Brier, Eduard; Vogt, Astrid; Mishra, Amaresh; Mena‐Osteritz, Elena; Bäuerle, Peter
Abstract A new class of π‐conjugated polycyclic hydrocarbons that promises interesting electronic properties is presented. The synthesis and extension of the S, N‐heteroacene series consisting of only five‐membered heterocyclic rings up to a very long, stable, and still soluble decacene SN10 is realized by multiple Pd‐catalyzed aminations of halogenated thiophene precursors as key reactions. These novel heteroacenes were characterized by optical spectroscopy and electrochemistry providing interesting structure–property relationships. Nearly complete bond‐length equalization in the inner part of the conjugated backbone and an unusual herringbone packing in the solid state underline the structural features of these novel systems.